A 21ST CENTURY “MOUSETRAP” – FROM HAMLET TO EDWARD SNOWDEN (Philological Studies, 2019)
The article focuses on methods of discipline, control and surveillance in Shakespeare's Hamlet, Ivo Brešan's play Acting Hamlet in the Village of Mrduša Donja (Predstava Hamleta u selu Mrduša Donja), and contemporary film adaptations of Hamlet (e.g. Michael Almereyda's Hamlet from 2000). The universal issues raised by the Renaissance play are analyzed with respect to Elizabethan ideology, totalitarian systems of the 20th century, and contemporary forms of surveillance in today’s „control societies“ (Deleuze). The article also comments on Edward Snowden as a sort of an „anti-Hamlet“ (Rae), who remains determined in his decision to make public the secret surveillance programs launched by the government.
Keywords: Hamlet, Acting Hamlet in the Village of Mrduša Donja, surveillance, „control societies“, Edward Snowden